Remaining Life Analysis of Pipeline Gas with Extreme Value Theory - Simeon, Rony Prayitno; Siradj, Eddy Sumarno; Kurniawan, Tedi (Journal of Materials Exploration and Findings, 2025)
Energy and chemical companies use pipelines to transfer oil, gas, and other materials from one place to another, within and between their plants. Pipeline integrity is an important concern because pipeline leakage could result in serious economic or environmental losses. Some research has applied to understand the effect of extrapolation value of the minimum thickness of pipeline by using the Extreme Value Theory. In this research, both statistical models and Extreme Value methods were applied and developed for the reliability of the pipeline by assuming the constant corrosion rate and deviation due to measuring devices were neglected. The research obtained that using the General Pareto Distribution technique, the result found that the extreme value method seems not close agreement with the Pareto Distribution. While using the Generalized Extreme Value Technique found remaining life of 344 blocks data of the pipeline around 5.23 years. It could be suggested that next pipeline pigging should be conducted within 2.5 years.